2013
DOI: 10.1111/josh.12058
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness, Academic Achievement, and Socioeconomic Status in School‐Aged Youth

Abstract: Compared with all other variables, SES appears to have the strongest association with academic achievement. However, it also appears that high fitness levels are positively associated with academic achievement in school-aged youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
1
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 27 publications
7
88
1
12
Order By: Relevance
“…It is important to highlight that in spite of all evidences shown in this study, the literature indicates that there is a link between academic performance and better physical fitness [3][4][5] and good aerobic capacity 1,21 . The intensity of the PA also appears to influence the academic performance 8,10,22 .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…It is important to highlight that in spite of all evidences shown in this study, the literature indicates that there is a link between academic performance and better physical fitness [3][4][5] and good aerobic capacity 1,21 . The intensity of the PA also appears to influence the academic performance 8,10,22 .…”
Section: Discussionmentioning
confidence: 63%
“…A study with American school children found a significant relationship between strength components and muscular endurance with higher grades and academic performance associated with physical activity of vigorous intensity 5 . In another research 1 , besides endurance (muscle resistance), a higher correlation coefficient was observed with aerobic fitness, in boys who were in the 'Healthy Fitness Zone' for aerobic conditioning and muscle strength.…”
Section: Introductionmentioning
confidence: 99%
“…Los hallazgos de este trabajo están en consonancia a los de la mayoría de investigaciones previas que revelan una asociación positiva de la capacidad aeróbica con la cognición (Aberg et al, 2009;Coe et al, 2013;Sardinha et al, 2014). Algunos estudios sugieren que una capacidad aeró-bica elevada podría estar asociada con mejoras en el cálculo matemático y en la resolución de problemas de aritmética (Moore et al, 2014), así como con mayor riqueza de palabras y sus significados, lo que determina un mayor nivel y control del lenguaje .…”
Section: Discussionunclassified
“…7 de ellos fueron transversales (Bass et al, 2013;Coe et al, 2013;Esteban-Cornejo et al, 2014;Janak et al, 2014;Planinsec y Pisot, 2006;Sardinha et al, 2014;Welk et al, 2010), 3 de intervención (Ardoy et al, 2014;Budde et al, 2008;Travlos, 2010), y 2 longitudinales (Chen et al, 2013;London y Castrechini, 2011). 1 tuvo un doble diseño transversal y longitudinal (Aberg et al, 2009).…”
Section: Figura 1 Flujo De Artículos a Través Del Proceso De Búsquedaunclassified
“…Keywords: physical activity; academic performance; health; physical education ANTECEDENTES En los últimos años, un creciente número de estudios han demostrado la relación positiva entre la práctica de actividad física (AF) y el rendimiento académico (RA) tanto en niños (Haapala, 2013;Torrijos-Niño et al, 2014) como en adolescentes (Ardoy et al, 2014;Coe et al, 2013). Sin embargo, tan solo un 20% de los adolescentes cumplen con la recomendación de la Organización Mundial de la Salud (OMS, 2014) de la práctica diaria de actividad física moderada a vigorosa (AFMV) durante al menos 60 minutos.…”
unclassified